Optimizing Asset Management of Kota Juang Public Market in Bireuen District: A GIS-Based Approach and Community Engagement - Jufriadi, Jufriadi; Alkhaly, Yulius Rief; Maizuar, Maizuar (International Journal of Multidisciplinary Approach Research and Science, 2025)
Managing the assets of the public market in Kota Juang, Bireuen District, must be implemented well to provide an overview of regional wealth, clarify ownership status, safeguard regional goods, and increase regional original income. This research aims to analyze the factors that most influence the less-than-optimal management of public market assets in Kota Juang, Bireuen District, in terms of the role of the market community for good operational sustainability in helping to develop traders' businesses and to find out which infrastructure facilities and infrastructure need to be revitalized. The management of public market assets in Kota Juang, Bireuen District, is optimized by implementing the Geographic Information System/GIS. There are four stages in using the GIS application. The first stage is the data input stage, which includes planning, determining goals, collecting data, and entering it into the computer. Then, the data processing and analysis stage, as well as the output stage, which is the final phase, is presented as a hardcopy map, data tabulation, or a website. The data inputted as attributes in this GIS application is obtained from observations at market locations and related agencies in the form of location maps, Figures of the condition/existing market assets, supporting infrastructure data, and data on traders in the market community. This research uses purposive sampling techniques and data analysis using SWOT analysis. From the results of partial hypothesis testing on building conditions where the t-count = 4.769, while the t-count for facilities and infrastructure is 5.756, this value is greater than the t-table, namely 2.014, so it significantly affects market asset management. The final result of the SWOT analysis is to overcome the problems in the public market area by planning the need for facilities and infrastructure or infrastructure that is no longer suitable so that it can be revitalized and increase the role of market managers by preparing standard operating procedures.